Analisis Kriminologis Cyberbullying dan Implikasinya terhadap Delik Pembunuhan Tidak Langsung - Danial fansuri (Jurnal Hukum Lex Generalis, 2025)
Cyberbullying is a cybercrime that contributes to the rising incidence of adolescent suicide. This study aims to analyze cyberbullying from a criminological perspective and examine its implications for the concept of indirect homicide. The research employs an empirical method with a socio-legal approach, involving interviews with victims, educators, and law enforcement officers, as well as observations of digital interactions. The findings indicate that repeated victimization, perpetrator anonymity, and weak social control trigger extreme psychological pressure leading to suicide. This study recommends strengthening regulations, developing responsive digital reporting mechanisms, and implementing school and family based prevention programs.